Colon Carcinogenesis: The Interplay Between Diet and Gut Microbiota - Loke, Yean Leng; Chew, Ming Tsuey; Ngeow, Yun Fong; Lim, Wendy Wan Dee; Peh, Suat Cheng (Frontiers in Cellular and Infection Microbiology, 2020)
Colorectal cancer (CRC) incidence increases yearly, and is three to four times higher in developed countries compared to developing countries. The well-known risk factors have been attributed to low physical activity, overweight, obesity, dietary consumption including excessive consumption of red processed meats, alcohol, and low dietary fiber content. There is growing evidence of the interplay between diet and gut microbiota in CRC carcinogenesis. Although there appears to be a direct causal role for gut microbes in the development of CRC in some animal models, the link between diet, gut microbes, and colonic carcinogenesis has been established largely as an association rather than as a cause-and-effect relationship. This is especially true for human studies. As essential dietary factors influence CRC risk, the role of proteins, carbohydrates, fat, and their end products are considered as part of the interplay between diet and gut microbiota. The underlying molecular mechanisms of colon carcinogenesis mediated by gut microbiota are also discussed. Human biological responses such as inflammation, oxidative stress, deoxyribonucleic acid (DNA) damage can all influence dysbiosis and consequently CRC carcinogenesis. Dysbiosis could add to CRC risk by shifting the effect of dietary components toward promoting a colonic neoplasm together with interacting with gut microbiota. It follows that dietary intervention and gut microbiota modulation may play a vital role in reducing CRC risk.